Development of Teaching Materials Based Learning Management System “Sifajargoro” to Foster Attitudes of Responsibility and Student Learning Outcomes in The Subjects of Civics Fifth Grade Elementary School Students - Anang Budiantara; Mustaji Mustaji; Raden Roro Nanik Setyowati (research, training and philanthropy institution Natural Aceh, 2023)
The background of this study is that the use of Google Classroom in elementary school spoon II Bojonegoro is considered less effective e. This study aims to determine: 1) the development process of teaching materials based on LMS